Nine Theses on Autonomy: Making Sense of a Controversial Doctrine - Enzo Cannizzaro (European Papers, 2024)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(3), 1317-1331 | Article | (Table of Contents) I. Introduction. – II. Autonomy in the early theories of sovereignty. – III. A historical hypothesis: autonomy as an institutional tool. – IV. The triumph of autonomy. – V. A change of paradigm: absolute autonomy v offene Staatlichkeit. – VI. Reverse autonomy. – VII. Autonomy of the EU vis-à-vis its Member States. –VIII. Autonomy vis-à-vis international law. – IX. Autonomy v Völkerrechtsfreundlichkeit. – X. The political dimension of autonomy. | (Abstract) The notion of autonomy sinks its roots in the dynamics between political sovereignty and legal sovereignty. Although autonomy, namely normative sovereignty, was perceived by the early theorists as an inseparable prerogative of the sovereign, its conceptual development took far more time than the notion of political sovereignty. Autonomy emerged at a later time in-keeping with the conception of a legal order, conceived of as a close system of rules proceeding from a fundamental rule conferring normativity to the whole system. In the process of the European integration, the notion of autonomy followed an inverse trajectory. Whereas the EU does not possess the prerogatives of political sovereignty, it developed into a normative entity independent vis-à-vis the legal orders of its Member States. But the transplant of this notion of absolute autonomy in the realm of international law could deeply affect the capacity of the EU to implement its international values enshrined in its Constitutional setting.